Penerapan aplikasi readle dalam pembelajaran keterampilan membaca siswa SMAN 1 Kertosono - Santoso, Natanael Victor; Usman, Rizman (Fakultas Sastra, 2023)
Abstrak: Reading skill is a skill needed in learning a language, including German. In learning German in high school, reading practice activities are divided into reading aloud and reading comprehension exercises. The results of observations before conducting the research, students of class XII IPA 2 SMAN 1 Kertosono had difficulty reading. These difficulties can be overcome with the Readle application, which contains reading texts, audio, explanations, quizzes, and translations in English. The purpose of this research is to apply the Readle application to train students' reading skills. This study used descriptive qualitative method. Research data were collected through observation and interviews. The results showed that the implementation of the Readle application went according to plan, the student responses were very positive, and students thought that they found it helpful in learning German by using the Readle application. This positive response indicates that the Readle application can be used in German learning activities at school because the various features provided by the application can be used for learning German reading, both reading aloud and reading comprehension. Kata Kunci: Readle App, Reading Skill, Mobile Learning